Past perfect [compact disc, unabridged] : a novel - Steel, Danielle (Recorded Books, Llc, 2017)
Leaving their well-ordered Manhattan life to move to San Francisco triggers a collision between the past and present for a successful married couple who, during a small earthquake, experience visions of their new home's original inhabitants from a century earlier.